THE EFFECT OF LIQUID ORGANIC FERTILIZER FROM FISH WASTE TO THE GROWTH AND YIELD OF KALE (Brassica oleracea var.sabellica) ON PEAT SOIL - Angela Purnamasari; Surachman .; Siti Hadijah (Jurnal Sains Pertanian Equator, 2019)
This study was aimed to obtain the best concentration of liquid organic fertilizer from fish waste to the growth and yield of kale on the field. The research was conducted from March 1st until April 16th, 2019 at the experiment field in Agriculture Faculty, Tanjungpura University, Pontianak. The research was used Completely Randomized Design (CRD) with the application of organic fertilizer as a single factor. The research was designed in 5 treatments of concentration and 5 replications, each replication consisted of 4 sample plants. The treatments consist of i1 = 300 ml / liter of water, i2 = 400 ml / liter of water, i3 = 500 ml / liter of water, i4 = 600 ml / liter of water, i5 = 700 ml / liter of water. The variables observed in this research consist of root volume, number of leaves, plant fresh weight, plant dry weight, and root dry weight. Based on the results of the research conducted, it can be concluded that the administration of liquid organic fertilizer from fish waste can increase the growth and yield of kale plants on peat soil. Giving concentration of liquid organic fertilizer from fish waste 600 ml/liter of water produces the highest number of leaves and a concentration of 700 ml/liter of water produces fresh weight and the highest dry weight of kale plants. The use of liquid organic fertilizer from fish waste with a concentration of 500 ml/liter of water showed the most efficient results for all observation variables.Keywords: fish waste, kale, liquid organic fertilizer, peat